Leaf-rolling sawflies (Hymenoptera, Pamphiliidae, Pamphiliinae) of Tianmushan Mountains, Zhejiang Province, China - Shinohara, Akihiko; Wei, Mei-Cai (Zootaxa, 2016)
Two species of Neurotoma, six species of Onycholyda, and five species of Pamphilius are recorded from Tianmushan, Zhejiang Province, China, and a key is given to these three genera and 13 species. Three new species, Onycholyda atra Shinohara & Wei, sp. nov. from Zhejiang Province, O. fulvicornis Shinohara, sp. nov. from Shaanxi Province and Zhejiang Province, and Pamphilius padus Shinohara, sp. nov. from Zhejiang Province, are described. New distribution records are: Onycholyda shaanxiana Shinohara, 1999, from Hubei Province, Zhejiang Province and Guangxi Zhuang Autonomous Region, O. subquadrata (Maa, 1944) from Zhejiang Province, O. tianmushana Shinohara & Xiao, 2006, from Hunan Province and Jiangxi Province, Pamphilius palliceps Shinohara & Xiao, 2006, from Anhui Province, P. lizejiani Shinohara in Shinohara & Wei, 2012, from Zhejiang Province, P. shengi Wei in Wei & Xiao, 1999, from Hubei Province and Zhejiang Province, and P. qinlingicus Wei in Wu & Wei, 2010, from Zhejiang Province. The larva of P. padus feeds on Padus obtusata (Rosaceae) and that of P. palliceps feeds on Rosa multiflora (Rosaceae), both singly making a leaf-roll. Rubus peltatus (Rosaceae) is recorded as a host plant of O. atra based on the observation of oviposition.